Bridging science and curriculum: preparing future leaders in computational toxicology - Hall, Frances; Johnson, Candice (Frontiers in Toxicology, 2026)
Computational toxicology plays an important role in chemical safety assessments. Computational methods are applied to early-stage screening in drug discovery, hazard identification, and regulatory safety assessment. This article presents an overview of the foundational skills, technical capabilities and regulatory literacy recommended to successfully apply and evaluate (Q)SAR ((Quantitative) Structure-Activity Relationship) methodologies (e.g., statistical and alert-based approaches) and read-across within established frameworks such as the (Q)SAR Assessment Framework (QAF), OECD validation principles and context-specific regulatory frameworks; for example, ICH M7. Additionally, the manuscript covers strategies that can be used to integrate theoretical and practical experience with foundational skills (e.g., internships, case studies, regulatory simulations). An overall educational framework that emphasises competency-based education through interdisciplinary exposure is presented. The framework outlines the progression from foundational knowledge to methodological understanding, context of use application and the ability to assess the reliability of outcomes. Although the integrated framework is applicable to both regulatory and non-regulatory use contexts, the manuscript presents regulatory focused use cases, which could be explored within educational settings. These use cases consider mature, as well as emerging regulatory applications, and therefore highlight the need to apply foundational principles (e.g., expert review, qualification of methods) in diverse contexts. This approach reinforces a context-of-use driven approach to curriculum design and provides opportunities for growth through real-world application and experiential learning, supported by collaborative initiatives and open-access resources.